Computer System - (:unkn) unknown (Coy C. Carpenter Library, 2008)
Published in: Topics. September 1963.
The first "modern" computer data processing system for the North Carolina Baptist Hospital and the Bowman Gray School of Medicine was installed in early 1964. The effective use of the computer system proved to be a remarkable benefit to the doctor and the hospital administrator but more importantly, the patient. Through the use of data processing, a physician was able to get much needed medical information in a matter of minutes, which reflected much better patient care. Shown here is a physician taking a computer tutorial course.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth